The geography of tourism and recreation : environment, place and space - Hall, Colin Michael, 1961-; Page, Stephen J. (London ; New York : Routledge, Taylor & Francis Group, 2014)
This fourth edition of The Geography of Tourism and Recreation provides students with a comprehensive introduction to the interrelationship between tourism, leisure and recreation from geographical and social science perspectives. It still remains the only book to systematically compare and contrast in a spatial context, tourism and recreation in relation to leisure time, offering insight into the demand, supply, planning, destination management and impacts of tourism and recreation. Whilst retaining its accessible style and approach this edition has been significantly updated to reflect recent developments and new concepts from geography which are beginning to permeate the tourism and recreational field.
Čtvrté, aktualizované vydání publikace nabízí komplexní úvod do geografie cestovního ruchu a rekreace z pohledu geografie a sociálních věd. Autoři systematicky analyzují vzájemné vztahy mezi cestovním ruchem, volným časem a rekreačními aktivitami v prostorovém kontextu a zabývají se poptávkou, nabídkou, plánováním, řízením destinací i dopady cestovního ruchu a rekreace na prostředí a společnost. Kniha reflektuje současné teoretické přístupy a nové koncepty v geografii, které ovlivňují výzkum i praxi v oblasti turismu a volnočasových aktivit.
Název z titulní obrazovky
Obsahuje bibliografii a rejstřík
Způsob přístupu: Internet
Keywords: geografie cestovního ruchu; rekreace; volný čas; sociologie cestovního ruchu; studie; geography of tourism; recreation; leisure; sociology of tourism; studies